The comparison of pregnancy outcomes in fresh and frozen embryo transfer: A cross-sectional study - Ramesh Baradaran Bagheri; Mahshid Bazrafkan; Abbas Sabour; Mina Ataei; Bita Badehnoosh; Banafsheh Mashak; Bahareh Khakifirooz; Ramin Moghaddam (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: The benefits of frozen embryo transfer (FET) vs. fresh embryo transfer for in vitro fertilization (IVF) have been discussed in previous studies. Objective: To determine and compare the pregnancy outcomes following FET and frozen embryo transfer in women who underwent assisted reproductive techniques. Materials and Methods: In this cross-sectional study, 233 women candidates for IVF/intra cytoplasmic sperm injection who referred to the Kamali Training Medical Center, Karaj, Iran during 2019-2020 were evaluated in 2 groups of fresh (n = 127) and frozen (n = 106) embryo transfers. The rates of pregnancy outcomes including chemical and clinical pregnancy, live birth, preeclampsia, ectopic pregnancy, still birth, and pregnancy loss were compared between groups in 3 age subgroups ( < 25, 25-35, and 35-40 yr old). Results: No significant difference in terms of chemical and clinical pregnancy and live birth rates were observed between groups in women aged < 25 yr. Chemical and clinical pregnancy and live birth rates were significantly higher in the FET group compared to fresh group in 25-35-yr-old women (p = 0.01, p = 0.03, and p = 0.01, respectively). In 35-40-yr-old women, no significant differences were observed in terms of chemical and clinical pregnancy rates, but live birth rate was found to be significantly higher in the FET group (p = 0.02). The pregnancy loss was lower in the FET group (p = 0.038). Conclusion: In conclusion, the FET method in women aged 25-35 yr significantly increases the chance of successful IVF/intra cytoplasmic sperm injection.